Double crosslinked biomimetic composite hydrogels containing topographical cues and WAY-316606 induce neural tissue regeneration and functional recovery after spinal cord injury - Xingchang Zhao; Xianzhe Lu; Kai Li; Shiqiang Song; Zhaohui Luo; Chuanchuan Zheng; Chengliang Yang; Xiumei Wang; Liqiang Wang; Yujin Tang; Chong Wang; Jia Liu (Bioactive Materials, 2023)
Spinal cord injury (SCI) is an overwhelming and incurable disabling condition, for which increasing forms of multifunctional biomaterials are being tested, but with limited progression. The promising material should be able to fill SCI-induced cavities and direct the growth of new neurons, with effective drug loading to improve the local micro-organism environment and promote neural tissue regeneration. In this study, a double crosslinked biomimetic composite hydrogel comprised of acellularized spinal cord matrix (ASCM) and gelatin-acrylated-β-cyclodextrin-polyethene glycol diacrylate (designated G-CD-PEGDA) hydrogel, loaded with WAY-316606 to activate canonical Wnt/β-catenin signaling, and reinforced by a bundle of three-dimensionally printed aligned polycaprolactone (PCL) microfibers, was constructed. The G-CD-PEGDA component endowed the composite hydrogel with a dynamic structure with a self-healing capability which enabled cell migration, while the ASCM component promoted neural cell affinity and proliferation. The diffusion of WAY-316606 could recruit endogenous neural stem cells and improve neuronal differentiation. The aligned PCL microfibers guided neurite elongation in the longitudinal direction. Animal behavior studies further showed that the composite hydrogel could significantly recover the motor function of rats after SCI. This study provides a proficient approach to produce a multifunctional system with desirable physiological, chemical, and topographical cues for treating patients with SCI.